Additive manufacturing method for preparing heterogeneous material, heterogeneous material and application
Synchronous deposition of metal welding wire and deteriorating agents through laser melting deposition technology, the problem of different properties of heterogeneous materials in the aerospace field is solved, and the efficient preparation of multi-performance heterogeneous materials is achieved, and the material waste and preparation cost is reduced. The obtained components are Uniform performance changes.
Patent Information
- Application Number
- CN202411527699.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-10-30
AI Technical Summary
The prior art is difficult to effectively prepare heterogeneous materials with different properties, especially in the aerospace field. The difference in material properties of roulettes and blades leads to low manufacturing efficiency and severe waste of materials. Traditional methods such as welding and physical connections have joint stresses and Problem of limited material types.
Using laser melt deposition technology, metal welding wire and deterioration agent are synchronized on the surface of the matrix. By adjusting the type and content of the deterioration agent, the microstructure of metal is regulated, and multi-performance additive manufacturing of heterogeneous materials is achieved.
The preparation of multi-performance heterogeneous materials is realized, which reduces material losses and preparation costs, and the obtained components are uniform in thickness, and the performance can be varied in width and height directions, making the process stable and easy to achieve.
Smart Images

Figure CN119115215A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of additive manufacturing, and in particular to an additive manufacturing method for preparing heterogeneous materials, heterogeneous materials and applications. Background Art
[0002] At present, the components in the aerospace field are developing in the form of structural functionalization and component integration. Some large integral components bear different loads in different positions and directions, which makes alloys with single performance have certain limitations in practical applications. It is necessary to develop alloy components that can meet different performance requirements in different parts to meet current development needs. The type and organization of metals determine the performance of alloy components. The use of different types of materials to manufacture multi-performance components has become a future development trend.
[0003] Take the spiral blade disk as an example. The spiral blade disk is mainly composed of a disk and blades. During the operation of the spiral blade disk, the disk part works at a low temperature and is mainly subjected to mechanical stress, which requires high mechanical strength and fatigue strength; the blade part works under high temperature rotation and is mainly subjected to centrifugal force and thermal stress, which requires oxidation resistance, high temperature resistance and creep performance. Due to the difference in the service environment of the disk and the blade, the material properties of the two are different. Therefore, the preparation of multi-performance heterogeneous materials with different performances in different positions is of great significance for the development of mechanical components.
[0004] At present, the methods of combining two or more metals or non-metallic materials with different properties to form multi-performance heterogeneous materials include: 1) welding, which is to melt and combine two or more different types of metals or non-metallic materials through a heat source to connect the metals. However, there may be problems such as wetting, complex interface reactions, the formation of brittle compounds, and joint stress during welding. 2) Physical connection, casting a single part separately, using milling and cutting mechanical processing methods, and forming a structure through screws, mortise and tenon joints, etc. This method is inefficient and will cause a large waste of materials. 3) Chemical reaction methods such as wet impregnation, in-situ loading, and electrochemical cyclic voltammetry are mainly for composite heterogeneous materials of nano-scale particles, and the types of materials and particle sizes are severely limited.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The object of the present invention is to provide an additive manufacturing method for preparing heterogeneous materials, heterogeneous materials and applications.
[0007] The present invention is achieved in that:
[0008] In a first aspect, the present invention provides an additive manufacturing method for preparing heterogeneous materials, comprising depositing a metal welding wire and a modifier on a substrate surface by laser melting; the mass ratio of the metal welding wire to the modifier is 92-98wt%:2-8wt%.
[0009] In a second aspect, the present invention provides a heterogeneous material, including one made by the additive manufacturing method of any one of the aforementioned embodiments.
[0010] In a third aspect, the present invention provides an application of the heterogeneous material according to the aforementioned embodiment in aviation machinery and equipment.
[0011] The present invention has the following beneficial effects:
[0012] The present invention provides an additive manufacturing method for preparing heterogeneous materials, heterogeneous materials and applications. By simultaneously feeding a modifier into the process of laser additive metal welding wire for deposition, the reliability of additive molding is ensured, and the metal microstructure effect is adjusted by adjusting the type and content of the modifier, thereby adjusting different positions of the heterogeneous material to have different properties, thereby realizing additive manufacturing of multi-performance heterogeneous materials. Compared with traditional manufacturing methods, the laser additive manufacturing method can be manufactured according to the size of the parts, reducing material loss and waste. The metal welding wire is used for main molding, and the modifier is used to adjust the additive, so that the preparation cost is reduced, and the obtained multi-performance heterogeneous material component has uniform thickness, and performance changes can occur in the width and / or height direction. The process is stable and easy to implement. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0014] Figure 1 A cross-sectional scanning electron microscope image of the material in the height direction obtained by the method provided in Comparative Example 1 of the present invention;
[0015] Figure 2 A scanning electron microscope image of a cross section in the height direction of a heterogeneous material obtained by the method provided in Example 1 of the present invention;
[0016] Figure 3 A magnified view of the metallographic structure of a heterogeneous material at different positions in the height direction obtained by the method provided in Example 1 of the present invention;
[0017] Figure 4 The grain length distribution diagram of the heterogeneous material prepared by the method provided in Example 1 of the present invention at different amounts of modifier added;
[0018] Figure 5 A microhardness cloud diagram of a heterogeneous material in the height direction obtained by the method provided in Example 1 of the present invention;
[0019] Figure 6 A microhardness cloud diagram of the material prepared by the method provided in Comparative Example 1 of the present invention in the height direction;
[0020] Figure 7 A line graph of the microhardness of a heterogeneous material in the height direction obtained by the method provided in Example 1 of the present invention;
[0021] Figure 8 A microhardness line graph of a heterogeneous material in the height direction obtained by the method provided in Comparative Example 1 of the present invention;
[0022] Fig. 9 A line graph showing the tensile strength and elongation of a heterogeneous material prepared by the method provided in Example 1 of the present invention at different amounts of modifier added;
[0023] Fig.10 Scanning electron microscope images of room temperature tensile fracture morphology of heterogeneous materials prepared by the method provided in Example 1 of the present invention with different amounts of modifier added;
[0024] Fig.11 A scanning electron microscope image of the co-deposition of a modifier and a metal welding wire of a heterogeneous material prepared by the method provided in Comparative Example 2 of the present invention;
[0025] Fig.12 This is a histogram of the microhardness of heterogeneous materials prepared by the method provided in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0027] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0028] In a first aspect, the present invention provides an additive manufacturing method for preparing heterogeneous materials, comprising depositing a metal welding wire and a modifier on a substrate surface by laser melting.
[0029] Preferably, the metal welding wire is loaded into the wire guide tube by means of side-axis wire feeding for additive manufacturing, and the modifier is added to the metal welding wire in the form of powder to change the microstructure and performance of the metal welding wire. Therefore, additive manufacturing is performed by means of coaxial powder feeding.
[0030] Preferably, the laser used in the laser melting deposition process is a single heat source. By using a single heat source, the equipment for additive manufacturing is simpler, and the metal welding wire is used for main body molding, and the modifier is used to adjust the additive, so that the preparation cost is reduced. The thickness of the obtained multi-performance heterogeneous material components is uniform, and performance changes occur in both horizontal and height directions. The process is stable and easy to achieve.
[0031] The mass ratio of the metal welding wire to the modifier is 92-98wt%:2-8wt%. It is understood that the sum of the mass ratios of the metal welding wire and the modifier should be 100%, that is, when the mass of the modifier accounts for 2wt%, the mass of the metal welding wire is 98wt%.
[0032] The present invention combines the advantages of high precision of laser powder feeding additive and high efficiency of laser wire feeding additive, realizes the simultaneous addition of wire and powder, and improves the utilization rate of materials and production efficiency. In addition, the microstructure and mechanical properties of the deposited layer can be regulated by changing the ratio of wire and powder and the addition position, and can be precisely manufactured according to the different performance requirements of different parts of different heterogeneous materials, providing a new idea for the preparation of composite metal materials. It has research and application significance in the additive manufacturing of large, complex, and multi-performance heterogeneous material components.
[0033] In an optional embodiment, the laser melting deposition includes depositing metal welding wire and a modifier layer by layer on the surface of the substrate, controlling the amount and type of modifier added in each deposited layer according to the properties of the heterogeneous material to be prepared, and cooling for 0.8 to 1.2 minutes after each layer is deposited before continuing the deposition. The purpose of cooling after each layer is deposited is to reduce the heat accumulation of each deposited layer, which is beneficial to controlling the organizational structure and properties of the deposited layer.
[0034] Preferably, the molten width of each layer of deposited metal welding wire and modifier is 4.95-5.18 mm, the molten height is 1.35-1.42 mm, and the thickness of deposited two layers of multiple metal welding wire and modifier is 2.7-2.84 mm. According to the heterogeneous material to be prepared, multiple depositions can be performed in the same deposition layer of the substrate in the horizontal direction during deposition, and the molten width of each deposition is 4.95-5.18 mm, and the molten height of each deposition is 1.35-1.42 mm; multiple layers can also be deposited in the height direction of the substrate, and the thickness of deposited two layers of multiple depositions is 2.7-2.84 mm.
[0035] Preferably, the elevation of each layer during deposition is the height of the first layer.
[0036] In an optional embodiment, the laser melting deposition process is carried out in an inert gas chamber, and the parameters of the laser melting deposition include: laser spot diameter 2-5 mm, laser power 1800-2400 W, scanning rate 80-180 mm / min, wire feeding speed 800-1400 mm / min, overlap rate 45-55%, shielding gas flow rate 45-55 L / min, powder feeding disk speed 0.04-0.08 r / min, powder carrier gas flow rate 6-8 L / min, and both shielding gas and powder carrier gas are inert gases.
[0037] Preferably, the protective gas and the powder carrier gas are both argon, and the oxygen content in the inert gas chamber is less than 50 ppm.
[0038] In an optional embodiment, the material of the metal welding wire includes at least one of titanium alloy, aluminum alloy or stainless steel, preferably titanium alloy.
[0039] Preferably, the material of the metal welding wire is the same as that of the substrate, so that the bonding ability between the metal welding wire and the substrate is better.
[0040] Titanium alloys include TC4 or TC11.
[0041] Preferably, the diameter of the metal welding wire is 1-2 mm, for example, 1.0 mm, 1.2 mm, 1.4 mm, 1.6 mm, 1.8 mm or 2.0 mm.
[0042] Preferably, the angle between the metal welding wire and the substrate is 15-25°, and the metal welding wire is aligned with the trajectory of the laser, and the welding wire head is located at the center of the laser processing head to ensure smooth welding.
[0043] In an optional embodiment, the modifier includes metal powder or ceramic particles, the metal powder includes Cu or Mo; the ceramic particles include TiC or ZrB2. The modifier is a material that can be combined with the metal welding wire to change the microstructure and performance of the deposited layer. The type and content of the heterogeneous agent can be adjusted according to the performance requirements of the heterogeneous material to be prepared, such as mechanical strength, plasticity, toughness, etc. to prepare the heterogeneous material.
[0044] Preferably, in order to adapt to the laser melting deposition technology and ensure the organizational structure and performance of the deposited layer, the particle size of the modifier is 50-150 μm, and the purity of the modifier is ≥99.5%.
[0045] Preferably, the modifying agent further comprises drying the modifying agent before laser melting deposition.
[0046] In an optional embodiment, the substrate includes at least one of a steel substrate, a titanium alloy substrate and an aluminum alloy substrate, preferably a titanium alloy substrate.
[0047] Preferably, the titanium alloy substrate includes TC4 or TC11.
[0048] In an optional embodiment, in order to make the bonding between the metal welding wire and the substrate more stable, the substrate is polished and cleaned before the laser melting deposition.
[0049] In an optional embodiment, polishing includes polishing with 400-1200 mesh sandpaper, and cleaning includes cleaning with alcohol or acetone.
[0050] In a second aspect, the present invention provides a heterogeneous material, including one made by the additive manufacturing method of any one of the aforementioned embodiments.
[0051] In a third aspect, the present invention provides an application of the heterogeneous material according to the aforementioned embodiment in aviation machinery and equipment.
[0052] Example 1
[0053] This embodiment provides an additive manufacturing method for preparing heterogeneous materials, comprising the following steps:
[0054] S01. Modifier pretreatment: Place the pure Cu powder of the modifier in a vacuum drying oven at 100° C. for 2 hours to remove moisture, and then set aside.
[0055] S02, substrate pretreatment: Use wire cutting to cut the TC4 substrate into a 100×300×20mm cuboid, then polish it flat with 400, 800 and 1200 mesh sandpaper respectively, and then use acetone and alcohol to clean the oil stains on the surface of the substrate to make the substrate surface to be deposited clean.
[0056] S03, feed the TC4 metal welding wire into the wire guide tube, adjust the wire guide nozzle angle of the wire guide tube to 20° with the substrate, and adjust the TC4 metal welding wire to be flush with the travel trajectory of the laser, and the welding wire head is in the center position of the laser processing head.
[0057] S04. The parameters for setting laser melting deposition include: laser spot diameter 3mm, laser power 2000W, scanning rate 120mm / min, wire feeding speed 1000mm / min, overlap rate 50%, shielding gas flow 50L / min, powder feeding disk speed 0.06r / min, powder carrier gas flow 7L / min. The laser melting deposition process is carried out in an inert gas chamber. The shielding gas and the powder carrier gas are both argon, and the oxygen content of the inert gas chamber is <50ppm.
[0058] S05. According to the parameters of step S03, TC4 metal welding wire and pure Cu powder as a modifier are laser melted and deposited on the surface of the TC4 substrate by using a side-axis wire feeding and a coaxial powder feeding method.
[0059] The deposited layer is divided into five regions according to the amount and type of the modifier added, wherein only TC4 metal welding wire is deposited in the first region to ensure a tight connection between the deposited layer and the substrate. Starting from the second region, pure Cu powder as a modifier is added to the TC4 metal welding wire, the mass proportion of the pure Cu powder in the second region is 2wt%, the mass proportion of the pure Cu powder in the third region is 4wt%, the mass proportion of the pure Cu powder in the fourth region is 6wt%, and the mass proportion of the pure Cu powder in the fifth region is 8wt%.
[0060] It should be noted that the direction from the first area to the fifth area is gradually away from the substrate. In each area, the number of deposited layers is multiple layers, and the height of the deposited layers in each area is 2 layers. The single-pass melt width of the deposited layer is 5.0 mm; the melt height is 1.4 mm, and the height of each deposited layer is the height of the first deposited layer.
[0061] The heterogeneous material prepared by the additive manufacturing method for preparing heterogeneous materials provided in this embodiment is a single wall of multi-performance heterogeneous titanium alloy, and the bottom length of the single wall is 69.23 mm, the top length is 39.62 mm, the height is 13.78 mm, and the thickness is 5.16 mm.
[0062] Example 2
[0063] This embodiment provides an additive manufacturing method for preparing heterogeneous materials, comprising the following steps:
[0064] S01. Modifier pretreatment: Place the pure Mo powder of the modifier in a vacuum drying oven at 100° C. for 2 hours to remove moisture, and then set aside.
[0065] S02, substrate pretreatment: Use wire cutting to cut the TC4 substrate into a 100×300×20mm cuboid, then polish it flat with 400, 800 and 1200 mesh sandpaper respectively, and then use acetone and alcohol to clean the oil stains on the surface of the substrate to make the substrate surface to be deposited clean.
[0066] S03. Feed the TC11 metal welding wire into the wire guide tube, adjust the wire guide nozzle angle of the wire guide tube to 20° with the substrate, and adjust the TC11 metal welding wire to be flush with the laser's travel trajectory, with the welding wire head in the center of the laser processing head.
[0067] S04. The parameters for setting laser melting deposition include: laser spot diameter 3mm, laser power 2000W, scanning rate 120mm / min, wire feeding speed 1000mm / min, overlap rate 50%, shielding gas flow 50L / min, powder feeding disk speed 0.06r / min, and powder carrier gas flow 7L / min. Among them, shielding gas and powder carrier gas are both inert gases, and the laser melting deposition process is carried out in an inert gas chamber. The inert gas is argon, and the oxygen content of the inert gas chamber is less than 50ppm.
[0068] S05. According to the parameters of step S03, TC11 metal welding wire and pure Mo powder as a modifier are laser melted and deposited on the surface of TC4 substrate by using the method of side-axis wire feeding and coaxial powder feeding.
[0069] The deposited layer is divided into five regions according to the amount and type of the modifier added, wherein only TC11 metal welding wire is deposited in the first region to ensure a tight connection between the deposited layer and the substrate. Starting from the second region, pure Mo powder as a modifier is added to the TC11 metal welding wire, the mass proportion of the pure Mo powder in the second region is 2wt%, the mass proportion of the pure Mo powder in the third region is 4wt%, the mass proportion of the pure Mo powder in the fourth region is 6wt%, and the mass proportion of the pure Mo powder in the fifth region is 8wt%.
[0070] It should be noted that the direction from the first area to the fifth area is gradually away from the substrate. In each area, the number of deposited layers is multiple layers, and the height of the deposited layers in each area is 2 layers. The single-pass melt width of the deposited layer is 5.0 mm; the melt height is 1.4 mm, and the height of each deposited layer is the height of the first deposited layer.
[0071] The heterogeneous material prepared by the additive manufacturing method for preparing heterogeneous materials provided in this embodiment is a single wall of multi-performance heterogeneous titanium alloy, and the bottom length of the single wall is 69.23 mm, the top length is 39.62 mm, the height is 13.78 mm, and the thickness is 5.16 mm.
[0072] Example 3
[0073] This embodiment provides an additive manufacturing method for preparing heterogeneous materials, which is similar to the method in Embodiment 1, except that the modifier is ZrB2.
[0074] Comparative Example 1
[0075] This comparative example provides an additive manufacturing method for preparing heterogeneous materials, which is similar to the method in Example 1, except that no modifier is added.
[0076] Test Example 1
[0077] The heterogeneous materials prepared in Examples 1 to 3 and Comparative Example 1 were analyzed for macroscopic morphology and cross-sectional morphology. Since the heterogeneous materials prepared in the above schemes are all modified by changing the type and / or addition amount of the modifier in the height direction, the cross-sectional morphology analysis is the cross-sectional morphology analysis in the height direction. The analysis was performed using a scanning electron microscope, and the following results were obtained: Figure 1 to Figure 5 Results shown.
[0078] Depend on Figure 1 It can be seen that the TC4 metal welding wire alone in comparative example 1 has four different regions due to the influence of heat accumulation and different heat dissipation rates during the deposition process. Among them, region d is the bottom of the deposition layer and is close to the matrix. The heat can be quickly dissipated through the matrix without remelting. The organization shows a β columnar crystal with obvious directionality, and the lamellar α phase inside the crystal is interspersed with fine α. Region c is the remelting zone. Due to the slow heat dissipation rate in region c, the heat accumulation of the deposition layer causes remelting in this area. Since the solidification process in this area is a non-equilibrium solidification process of high-speed cooling, the length of the lamellar α phase between layers is reduced compared with other positions. Regions a and b are located at the top of the deposition layer. They are regions generated by different heat dissipation rates under the same heat accumulation. The organizational morphology of this area has both smaller β grains, and the lamellar α inside the grains are continuously arranged in the same direction to form a widmanstatten structure. There are also a certain number of discontinuous primary α grains on the β phase matrix. During the deposition process, the metal liquid is unevenly distributed, the grain size in region b is smaller than that in region a, and more dendrites that penetrate the grains are formed. However, in general, although the component of Comparative Example 1 forms multiple regions in the microstructure, the overall metallographic structure of each region is still composed of α phase and β columnar crystals.
[0079] According to Figure 2 and Figure 3 It can be seen that Figure 2 The a-d area is the TC4-Cu deposition layer, and the e area is the pure TC4 deposition layer. a is the top area of the deposition layer. Under the combined effect of faster cooling rate and Cu on grain refinement, equiaxed crystals are formed in this area. CuTi2 compounds appear in the interlayer transition zone. Under the effect of CuTi2, the grain size is small. The specific organization is shown in Figure 3 a. Equiaxed crystals are also formed in the location of area b. Compared with area a, more secondary α phases appear in the grains. Figure 3 b. Area c is in the middle layer of multiple deposition layers. The imbalance of heat input and output causes heat accumulation in this area, resulting in remelting. CuTi2 migrates to the interlayer remelting zone, resulting in uneven distribution of elements and tissues between layers. Part of the β grain boundary is retained in the interlayer position, and small clusters or flakes of α are distributed around the grain boundary. The specific organization is shown in Figure 3c. The d area is also a remelting area. This area is closer to the substrate and has a smaller heat accumulation effect. Therefore, the remelting degree is smaller than that of the c area. For specific organization, see Figure 3 d. Area e is a pure TC4 deposition layer. This area is close to the substrate. The absorbed laser heat can be quickly dissipated through the substrate without remelting. This area is distributed with a basket-like structure formed by interlacing β columnar crystals and needle-shaped α crystals with obvious directionality. The closer to the substrate, the larger the aspect ratio of the needle-shaped α crystals. For specific structures, see Figure 3 e and Figure 3 f.
[0080] The addition of pure Cu powder as a modifier increases in the deposition layer of Example 1 of the present invention in the height direction away from the substrate. Therefore, in the microstructure morphology, it is observed that the α phase formed by the TC4 metal welding wire transforms into martensite α', and Cu and Ti combine to form CuTi2 compounds, which are distributed in the top deposition layer and the fusion zone. Due to the high density of CuTi2, it moves to the fusion zone under the action of gravity, and the formation of CuTi2 will also cause the grains to become smaller. For example, in the d area, 2wt.% of pure Cu powder is added, and a small amount of columnar primary β grains exist in the organization, but their size is much smaller than that of the deposition sample without adding Cu, such as the e area; in the c area, when the content of pure Cu powder exceeds 4wt.%, the columnar grains disappear and are replaced by fine equiaxed grains. As the Cu content further increases, the size of the equiaxed grains in the b area and the a area also decreases.
[0081] Please refer to Figure 4 , the grain size of the heterogeneous material of Example 1 is specifically analyzed, wherein Figure 4 a is the grain distribution diagram of the deposited sample of pure TC4 metal welding wire, Figure 4 b is the grain distribution diagram of the deposited sample after adding 2wt% pure Cu powder. Figure 4 c is the grain distribution diagram of the deposited sample after adding 4wt% pure Cu powder. Figure 4 d is the grain distribution diagram of the deposited sample after adding 6wt% pure Cu powder. Figure 4 e is the grain distribution diagram of the deposited sample after adding 8wt% pure Cu powder.
[0082] In the deposited sample without Cu addition, there are a small number of small grains, mainly small equiaxed grains at the top, while other areas of the sample are dominated by coarse columnar grains. The grain length is mainly distributed in the range of 500-2000μm, and there are a small number of extremely coarse columnar primary β grains, whose length even exceeds 4000μm. When 2wt.% Cu is added, the maximum grain length drops to below 1400μm, and the grain length distribution is mainly concentrated in the range of 100-500μm. When the Cu content is 4wt.%, only a few grains exceed 1000μm in length, and the grain length distribution is more uniform. When the Cu content exceeds 6wt.%, the grains are further refined, and more than 75% of the grains are refined to 100-300μm in length, and only a small number of grains exceed 600μm in length, but when the Cu content exceeds 8wt.%, it can be observed that the effect of Cu on grain size refinement is no longer obvious.
[0083] Please refer to Fig.11 and Fig.12 ,in Fig.11 a is the microstructure of the deposited sample of pure TC4 metal welding wire. Fig.11 b is the microstructure of the deposited sample after adding 5wt% ZrB2 powder. Fig.11 c is the microstructure of the deposited sample after adding 10wt% ZrB2 powder. Fig.11 d is the microstructure of the deposited sample after adding 15wt% ZrB2 powder. Fig.11 e is the microstructure of the deposited sample after adding 20wt% ZrB2 powder. Fig.11 f is the microstructure of the deposited sample after adding 5wt% ZrB2 powder Fig.11 A magnified view of b. Fig.11 In the pure TC4 deposition sample of a, long strip-shaped grains can be seen, and the grains are also relatively coarse. After adding 5w% ZrB2 powder, Fig.11 In b, we can see that the coating has a ring structure that is connected end to end. The ring structure interrupts the continuous growth of the grains and produces relatively fine grains. When the f area is enlarged, we can see that the ring structure is composed of densely arranged white fine particles, such as Fig.11 f. The white particles are the TiB reinforcement phase generated in situ by the B element deposition sample and Ti in the molten ZrB2. With the increase of ZrB2 powder content, the main microstructure changes from the white ring structure of 5w% ZrB2 to the fishbone parallel structure of 10w% ZrB2, as shown in Fig.11 When the content of ZrB2 powder exceeds 10%, the white short rod-shaped and long strip-shaped structures are staggered and evenly distributed, indicating that the ZrB2 modifier provided in Example 3 also has a good tissue strengthening effect.
[0084] Fig.12 The microhardness of the heterogeneous material of Comparative Example 2 is shown. The microhardness of the pure TC4 coating is 450.0HV. With the addition of ZrB2, the microhardness of the deposit gradually increases. When 20wt% ZrB2 is added, the increase in the microhardness of the coating is the most significant, reaching 597.1HV, which is 32.7% higher than that of the pure TC4 deposited sample. This is attributed to the particle strengthening of the TiB reinforcement phase formed by the undissolved ZrB2 and the B element in the molten ZrB2 and the Ti element, as well as the solid solution strengthening effect of Ti-Zr.
[0085] Test Example 2
[0086] The mechanical properties of the heterogeneous materials prepared in Examples 1 to 3 and Comparative Example 1 were tested and the results were as follows: Figures 5 to 10 The results are shown in Figure 1. In Example 1 of the present invention, a modifier is added to the metal welding wire using laser melting deposition technology, and the obtained heterogeneous titanium alloy material has higher hardness, better tensile properties and excellent elongation.
[0087] Further, by Figure 5 and Figure 6 The microhardness of the heterogeneous materials of Example 1 and Comparative Example 1 in the vertical direction are shown respectively. Figure 5 and Figure 6 It can be seen that in Example 1, pure Cu powder is added as a modifier. After the modifier is added, the hardness of the material is significantly improved. Figure 7 and Figure 8 The results shown by Figure 7 and Figure 8 It can be seen that after adding pure Cu powder as a modifier in Example 1, the microhardness of the remelting zone reaches about 550Hv, while in Comparative Example 1, no modifier is added, and the microhardness of the remelting zone is only 450-480Hv; the hardness of the top of Example 1 can reach about 625Hv, while that of Comparative Example 1 is only 550-575Hv. At the same time, when the content of the modifier changes, the microhardness of the heterogeneous material of Example 1 changes greatly, and a hardness leap is achieved from the pure TC4 layer to the remelting zone, and another hardness leap is achieved from the remelting zone to the top fine grain zone. The above changes in microhardness are related to the changes in the organizational structure of the deposited layer. The organization of the pure TC4 deposited layer is mainly columnar crystals and basket-shaped α organization, and the grains are relatively coarse. The Cu-containing deposited layer has refined grains under the action of Cu, and element migration occurs at the top of the deposited layer. The Cu content at the top is higher than that of the rest, and the grain size is further reduced. The microhardness increases with the reduction of the grain size.
[0088] Fig. 9The figure shows the changes in tensile strength and elongation of the heterogeneous material of Example 1 as the content of the modifier increases. Among them, as the Cu content increases, the tensile strength increases and the elongation decreases, which is suitable for preparing some components with high strength requirements.
[0089] Fig.10 The results of tensile fracture morphology analysis of the heterogeneous material of Example 1 as the content of the modifier increases are shown. Fig.11 It can be seen that the TC4 fracture surface is a typical ductile fracture morphology, with a large number of equiaxed dimples distributed, shallow small dimples surrounding deeper large dimples, the inside of the dimples is smooth, and no second phase particles are found. The dimple depth in the TC4+2wt.%Cu structure becomes shallower, indicating that the plasticity of the sample decreases, and a small number of tear ridges appear. The fracture mechanism is a mixed fracture mechanism of ductile fracture and quasi-cleavage fracture. When the Cu content is 4wt.%, the fracture mode changes to quasi-cleavage fracture, the number of dimples is greatly reduced, and there are a large number of high-density short and curved tear ridge lines on the fracture surface, and a small number of cleavage steps appear. When the Cu content exceeds 6wt.%, although the fracture mechanism is still quasi-cleavage fracture, the dimples basically disappear, indicating that the brittle characteristics of the sample are obvious and the plasticity is seriously reduced. Therefore, it is suitable for the preparation of some high-strength materials.
[0090] The detection method in the above test example includes: using wire cutting to prepare metallographic samples and tensile samples, corroding with a mixed etching solution of hydrofluoric acid and nitric acid, and observing the structure of each area of the titanium alloy single wall with an optical microscope (OM); using a ZEISSGemini 300 high-resolution scanning electron microscope to perform structural element analysis on the cladding layer; using a DHV-1000ZTEST micro-Vickers hardness tester (136° regular quadrangular pyramid diamond indenter, pressure 9.8N, pressure holding 15s) to test the hardness of the sample.
[0091] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An additive manufacturing method for preparing heterogeneous materials, characterized in that: It includes using laser melting deposition to simultaneously deposit a metal welding wire and a modifying agent on the surface of a substrate; The mass ratio of the metal welding wire to the modifier is 92-98wt%:2-8wt%.
2. The additive manufacturing method for preparing heterogeneous materials according to claim 1, characterized in that: The laser melting deposition comprises depositing metal welding wire and modifier layer by layer on the surface of the substrate, and cooling each layer for 0.8 to 1.2 minutes after the deposition is completed before continuing the deposition; Preferably, the melt width of each layer of deposited metal welding wire and modifier is 4.95-5.18 mm, the melt height is 1.35-1.42 mm, and the thickness of deposited two layers of multi-pass metal welding wire and modifier is 2.7-2.84 mm; Preferably, the elevation of each layer during deposition is the height of the first layer.
3. The additive manufacturing method for preparing heterogeneous materials according to claim 1, characterized in that: The laser melting deposition process is carried out in an inert gas chamber, and the parameters of the laser melting deposition include: laser spot diameter 2-5 mm, laser power 1800-2400 W, scanning rate 80-180 mm / min, wire feeding speed 800-1400 mm / min, overlap rate 45-55%, shielding gas flow 45-55 L / min, powder feeding disc speed 0.04-0.08 r / min, powder carrier gas flow 6-8 L / min, and both the shielding gas and the powder carrier gas are inert gases; Preferably, the protective gas and the powder carrier gas are both argon, and the oxygen content in the inert gas chamber is less than 50 ppm.
4. The additive manufacturing method for preparing heterogeneous materials according to claim 1, characterized in that: The material of the metal welding wire includes titanium alloy or stainless steel, preferably titanium alloy; The titanium alloy includes TC4 or TC11; Preferably, the diameter of the metal welding wire is 1 to 2 mm; Preferably, the angle between the metal welding wire and the substrate is 15-25°.
5. The additive manufacturing method for preparing heterogeneous materials according to claim 1, characterized in that: The modifier includes metal powder or ceramic particles, the metal powder includes Cu or Mo; the ceramic particles include TiC or ZrB2; Preferably, the particle size of the modifier is 50-150 μm, and the purity of the modifier is ≥ 99.5%; Preferably, the modifying agent further comprises drying the modifying agent before the laser melting deposition, so as to prevent moisture from affecting the forming quality and fluidity.
6. The additive manufacturing method for preparing heterogeneous materials according to claim 1, characterized in that: The substrate comprises at least one of a steel substrate, a titanium alloy substrate and an aluminum alloy substrate, preferably a titanium alloy substrate; Preferably, the titanium alloy substrate includes TC4 or TC11.
7. The additive manufacturing method for preparing heterogeneous materials according to claim 6, characterized in that: The substrate is polished and cleaned before laser melting deposition.
8. The additive manufacturing method for preparing heterogeneous materials according to claim 7, characterized in that: The polishing includes polishing with sandpaper of 400-1200 meshes, and the cleaning includes cleaning with alcohol or acetone.
9. A heterogeneous material, characterized in that: The method is prepared by the additive manufacturing method according to any one of claims 1 to 8.
10. Use of the heterogeneous material according to claim 9 in aviation machinery and equipment.
Citation Information
Patent Citations
Double-side laser welding method for powder metallurgy control
CN105728944A
Composite-particle-strengthened metal powder core welding wire for manufacturing CMT electric arc additional materials and preparation method and application of welding wire
CN111203670A
Method for in-situ preparation of metal-based composite material through laser additive
CN111940730A
Silk powder composite laser additive manufacturing system and quality feedback regulation and control method
CN117816981A
Titanium alloy composite material and preparation method thereof
CN118180574A
